2005
DOI: 10.7748/ns2005.05.19.34.41.c3859
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ and doctors’ knowledge of pain after surgery

Abstract: Staff and patient misconceptions, inadequate sources of learning and professional traditions continue to affect the quality of acute pain management. However, progress has been made in the trust to overcome these factors through collaborative practice, review of education programmes and specific practice development initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 0 publications
2
39
0
7
Order By: Relevance
“…BLBK046-Cox July 24, 2008 13:46 Perioperative Pain Management (Chiu et al 2003, Coulling 2005 and studies concerning beliefs about pain continue to highlight misconceptions, such as neurologically impaired infants feeling less pain (Breu McGrath 2006). Knowledge, beliefs and attitudes comprise a dominant combination which can impede the delivery of good interventions.…”
Section: Assessing Painmentioning
confidence: 99%
“…BLBK046-Cox July 24, 2008 13:46 Perioperative Pain Management (Chiu et al 2003, Coulling 2005 and studies concerning beliefs about pain continue to highlight misconceptions, such as neurologically impaired infants feeling less pain (Breu McGrath 2006). Knowledge, beliefs and attitudes comprise a dominant combination which can impede the delivery of good interventions.…”
Section: Assessing Painmentioning
confidence: 99%
“…In achieving the goal of pain management, nurses have numerous responsibilities and shouls have adequate knowledge required (Craige, 2014;Coulling, 2005;Courtenay and Carey, 2008). Zhang et al (2008) stated that many nurses lack pain management knowledge and a varying number of studies indicated knowledge deficits and inadequate pain assessment as the most important barriers for health care professionals in implementing pain management.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, health professionals have an ethical duty to ensure pain in children is recognised and managed effectively (Olmstead et al 2010). Although effective pain management is dependent on collaboration across the multi-professional team (The Royal College of Paediatrics and Child Health 1997, Coulling 2005, RCN, 2009, nurses have 24 hour contact with hospitalised children and often assume the overall responsibility for the management of children's pain.…”
Section: Introductionmentioning
confidence: 99%